Power-law scaling of correlations in statistically polarised nano-NMR - Nicolas Staudenmaier; Anjusha Vijayakumar-Sreeja; Santiago Oviedo-Casado; Genko Genov; Daniel Cohen; Daniel Dulog; Thomas Unden; Nico Striegler; Alastair Marshall; Jochen Scheuer; Christoph Findler; Johannes Lang; et al. (npj Quantum Information, 2022)
Abstract Diffusion noise is a major source of spectral line broadening in liquid state nano-scale nuclear magnetic resonance with shallow nitrogen-vacancy centres, whose main consequence is a limited spectral resolution. This limitation arises by virtue of the widely accepted assumption that nuclear spin signal correlations decay exponentially in nano-NMR. However, a more accurate analysis of diffusion shows that correlations survive for a longer time due to a power-law scaling, yielding the possibility for improved resolution and altering our understanding of diffusion at the nano-scale. Nevertheless, such behaviour remains to be demonstrated in experiments. Using three different experimental setups and disparate measurement techniques, we present overwhelming evidence of power-law decay of correlations. These result in sharp-peaked spectral lines, for which diffusion broadening need not be a limitation to resolution.